Mentoring and Coaching Report: AICCRA Zambia-Aquaculture Bundle - Sichone, Mercy; Lundeba, Mary; Kanyembo, Henry; Mudege, Netsayi (WorldFish, 2025)
This report documents the coaching and mentoring support provided to Toda Raba Private Limited (a bundle partner under the AICCRA project) by WorldFish. Toda Raba Private Limited is a scaling partner under Bundle 2: Promoting integrated aquaculture agriculture systems through the dissemination of CIS and production of high-value fingerlings and farmed fish.